01/13/2008, 01:14 PM

To make it shorter:

h(i^(1/i)) = 1/i

h((1/i)^i) = i

-ith root of -i = selfroot of -i = reverse to infinite tetration of ((1/i)^(i)) = e^(pi/2)

ith root of i = selfroot of i = reverse to infinite tetration of ((i^(1/i))= e^pi/2

Self roots of both i and - i are equal and give 3 new values in one given combination: e, pi and 1/2 plus 4th value 4,81......... .

h(i^(1/i)) = 1/i

h((1/i)^i) = i

-ith root of -i = selfroot of -i = reverse to infinite tetration of ((1/i)^(i)) = e^(pi/2)

ith root of i = selfroot of i = reverse to infinite tetration of ((i^(1/i))= e^pi/2

Self roots of both i and - i are equal and give 3 new values in one given combination: e, pi and 1/2 plus 4th value 4,81......... .